Switchable surface coating for bifunctional passive radiative cooling and solar heating - Fei, Jipeng (2022)
The ability to achieve dual-mode thermal regulation for switchable heating and cooling on a single platform has thus far been challenged by the availability of suitable materials. The materials need to possess both high solar reflectance and high transmittance, necessitating large and small thicknesses in the same coating layer, respectively (i.e., the thickness constraint). Herein, for the first time, a single-layer coating made in a facile one-step process is reported, which exhibits rapid switch between high solar reflection (≈96.6%) and high solar transmission (≈86.6%). In the dry state, high solar reflectance and infrared (IR) emittance (>96% from 8 to 13 µm) enable passive radiative cooling, resulting in all-day near/sub-ambient temperatures in the demanding weather conditions of the tropical climate. Upon wetting, high transparency in the broadband range (0.3–2.5 µm) allows solar heating, leading to switchable thermal regulation. Such unprecedented performances are achieved through a unique hierarchical porous structure comprising of vertically aligned microscale pores in nanoscale pore matrix. This structure breaks the thickness constraint and broadens its applicability, in particular for seasonal areas with large temperature variation throughout the day.